Derviški obred sagledan iz etnomuzikološke i rodne perspektive. Primjer derviškog reda Rufai u Hrvatskoj - Rubić, Tihana (2008)
The paper is based on observation and narrative interviews, both particular anthropological fieldwork methods. The short-term ethnographic fieldwork was conducted among dervishes of the Rufai order, placed in Pehlin (improvised settlement, town of Rijeka, Adriatic Coast) while celebrating Nevruz (22.3.). In this paper we examine the ways in which the self-identity is constructed throughout the fact of having specific musical skills, or, on the other hand, being a woman.